84.2k views
4 votes
What is the value of a(b - c) when b = 3, c = -3 and a = -2?​

2 Answers

5 votes

Answer: -12

Explanation: It's a good idea to get into the habit of

using parenthses when substituting numbers in for variables.

If you have parenthses in your original problem,

change them to brackets as you substitute to avoid confusion.

Since your brackets replace your original parenthses,

your first step will be to simplify what's inside the brackets.

So we have (-2) [(3) - (-3)].

Simplifying inside the brackets, we get 6.

So we have (-2) [(6)].

Multiplying from here, our answer is -12.

User Datageist
by
5.2k points
3 votes

Answer:

-12

Explanation:

a(b - c)

b = 3, c = -3 and a = -2

-2( 3- -3)

-2(3+3)

-2(6)

-12

User AaronJPung
by
5.2k points